Cis-[Ni(?-Ox)(H2o)2]?: Metal Organic Coordination Polymer Assembled by Oxalate Ligand: Structural and Magnetic Characterization - Venegas-Yazigi, D; Venegas-Yazigi, D (2011)
In this work, we describe for first time, the structure and magnetic characterization of the one dimensional catena cis-[Ni(?-ox)(H 2O)2]? (1), which was obtained by solvothermal synthesis. Cis-[Ni(?-ox)(H2O)2] ? crystallizes in a C2/c spatial group. The asymmetric unit contains only one type of nickel atom, oxalate ligand and water molecules. The chain backbone is constructed by the bis-chelating coordination mode of the oxalate ligand, presenting a zigzag chain in the [1 0 1] direction. The nickel ions have a distorted octahedral geometry, surrounded by six oxygens, four of them from two different oxalate ligands and the other two from the cis-coordinated water molecules. Thermal dependence of the magnetic susceptibility of (1) was studied in a temperature range of 2.5-255 K, at applied fields of 0.10 and 0.25 kOe. The plot of ?MT(T) shows antiferromagnetic interactions between the Ni(II) centres. The experimental data were fitted between 255 and 30 K, using an empirical expression for a chain of equally spaced Ni(II) centres. The best fit of the experimental date gave a J value of -57 cm-1, which is much higher that the obtained for the trans-analogue. Irreversibility between ZFC and FC measurements below 9 K was observed, indicating some kind of magnetic ordering. © 2011 Elsevier B.V. All rights reserved.
Keywords: Antiferromagnetic Ni(II) oxalate chain; Crystal structure; Magnetic characterization